Incidence of poultry diseases in different seasons in Khushab district, Pakistan (Journal of Advanced Veterinary and Animal Research, 2015)
A field study was conducted to determine the prevalence of various poultry diseases in broilers and layers at Khushab district in Pakistan. The prevalence study was conducted in 360 poultry farms. Diagnosis of diseases in poultry was done based on history, clinical signs, post-mortem examination, cultural, and biochemical characterization. Overall, incidence of Newcastle disease (ND) was found as the highest (avg. 7.85%) in broiler, followed by Fowl typhoid (avg. 6.58%), Mycoplasma (avg. 5.68%), Escherichia coli infection (avg. 5.52%), Coccidiosis (avg. 4.59%), Mycotoxicosis (avg. 4.56%), Infectious Bursal Disease (IBD; avg. 2.84%), Infectious coryza (avg. 2.50%), Hydropericardium syndrome (HPS; avg. 1.67%), and Infectious bronchitis (IB; avg. 1.59%). The period during April to June appeared to be comparatively safer for the broilers as low incidence of disease was recorded at this period. In case of layers, incidence of ND was the highest (avg. 7.92%), followed by Fowl typhoid (avg. 6.97%), Mycotoxicosis (avg. 5.52%), Coccidiosis (avg. 4.75%), IBD (avg. 3.17%), Mycoplasmosis (avg. 3.0%), Infectious coryza (avg. 2.52%), Fowl cholera (avg. 1.52%), IB (avg. 0.90k%), E. coli infection (avg. 0.73%), and HPS (avg. 0.46%). For layers, the period during January to March appeared to be safer. In conclusion, diversified diseases are prevalent in both layers and broilers. Thus, proper vaccination practices, brooding arrangements, preventive measures, and biosecurity practices are recommended. http://dx.doi.org/10.5455/javar.2015.b65